Não - Palavras - Santos, Tábita Cristina Martins e (2019)
This dissertation has the proposal to discuss the importance of the not yet appeared words - in the standard lexicon - as tools to fight for equal rights for social minority groups and to understand this as an important space for social movements and struggles. Besides noticing the necessity of the emerging of words, or to at least save the spot for them, in order to diagnose society's issues that are not treated due to the lack of lexical recognition, providing progress and changes in political constructions and in the common sense. Therefore, this essay, looking at a specific group, researched all the Brazilian legislation directed to the disabled person in order to reach which words were added after the creation of certain laws, as well as how they evolved - such as accessibility and universal design - and your fundamental meanings. Seeking to comprehend the dynamics between people who alter the meanings of words and words that modify people and the social duel laid down from them. By comparing texts, legislations and historical contexts of this groups, we are proposed to query how far the words are determining and reductionist of the world, in order to highlight the importance to draft new models by creating "new meanings", symbolic struggles and new words.